Toxicity Tests of Botanical Pesticide Made of Tuba Root Extract on Spodoptera frugiperda - Mukhlis Ibrahim; Edhi Martono; Siwi Indarti (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2023)
One of the main pests that attack corn plants is Spodoptera frugiperda J. E. Smith. The usual control of this pest is by using synthetic insecticides, but the continuous or unwise use of synthetic insecticides will have negative impacts on humans and the environment, therefore alternative insecticides that are safe and environmentally friendly, such as tuba root (Derris elliptica Benth) are needed. This study aims to determine the effect of tuba root extract phytopesticide on S. frugiperda larvae and to determine the concentration of tuba root extract that is effective in controlling S. frugiperda larvae, as well as the eating inhibition power of S. frugiperda larvae after administration. The research was conducted at the Applied Entomology Laboratory, Faculty of Agriculture, Universitas Gadjah Mada, Yogyakarta from September to November 2022. The treatment concentrations used were 0, 2, 4, and 8 mL.L-1 of water. The experiment employed Completely Randomized Design (CRD) with four treatments and five replications. The results showed that the concentration of 4 mL.L-1 of water is an effective concentration for controlling S. frugiperda larvae and can cause a total mortality of 82% with an initial death of 19 hours, Lethal Time 50 at 39.20 hours after application. In addition, the concentration of tuba root powder extract of 8 mL.L-1 of water appeared to be the highest in reducing the appetite of larvae compared to other treatments with a rate of 17.03%. This showed the highest reduction in larval appetite compared to other treatments. A small amount of feed eaten means a high level of antifeedant activity.